2019
DOI: 10.3847/1538-4357/ab2881
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Lyα Nebula and a Small-scale Clumpy Outflow in the System of the Exotic Quasar J0952+0114 Unveiled by MUSE

Abstract: The well-known quasar SDSS J095253.83+011421.9 (J0952+0114) at z=3.02 has one of the most peculiar spectra discovered so far, showing the presence of narrow Lyα and broad metal emission lines. Although recent studies have suggested that a proximate damped Lyα absorption (PDLA) system causes this peculiar spectrum, the origin of the gas associated with the PDLA is unknown. Here we report the results of observations with the Multi Unit Spectroscopic Explorer (MUSE) that reveal a new giant (≈100 physical kpc) L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
(34 reference statements)
4
27
0
Order By: Relevance
“…This is consistent with the bright B16 sample shown in the same figure, and the results of Arrigoni Battaia et al (2019). As a viability check we have included the exotic quasar of Marino et al (2019). This broad line quasar lacks a broad Ly line as it is totally absorbed by a pDLA.…”
Section: Correlations Between Nebula and Qso Ly Emissionsupporting
confidence: 86%
See 3 more Smart Citations
“…This is consistent with the bright B16 sample shown in the same figure, and the results of Arrigoni Battaia et al (2019). As a viability check we have included the exotic quasar of Marino et al (2019). This broad line quasar lacks a broad Ly line as it is totally absorbed by a pDLA.…”
Section: Correlations Between Nebula and Qso Ly Emissionsupporting
confidence: 86%
“…In Marino et al (2019) it was observed that in the Ly surface brightness and kinematics there was no change in behaviour at small radii, suggesting that either the contribution from the ISM was negligible or there was a smooth transition from the CGM to the ISM. If the same behaviour extends to our faint sample and the narrow central emission is coming from the inner extent of the nebulae then we cannot determine if the emission arises from the ISM or CGM.…”
Section: Correlations Between Nebula and Qso Ly Emissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data points have been slightly shifted along the x-axis, for the sake of clarity. The average surface brightness profiles of the extended emission around quasars at z∼2.27 (magenta line; Cai et al 2019), z∼3.21 (light blue line; Arrigoni Battaia et al 2019a), and z∼3.36 (olive green line; Marino et al 2019) are also plotted. The corresponding exponential best fits are shown in the same color palette.…”
Section: The Average Surface Brightness Profilementioning
confidence: 99%